Use of Complementary and Alternative Medicine in Bayamón, Puerto Rico - Torres-Zeno, Roberto E.; Ríos-Motta, Ruth; Rodríguez-Sánchez, Yelitza; Miranda-Massari, Jorge R.; Marín-Centeno, Heriberto (Puerto Rico Health Sciences Journal, 2016)
Objective: To profile complementary and alternative medicine (CAM) utilization patterns in the municipality of Bayamón, Puerto Rico. Methods: The study consisted of a cross-sectional household survey conducted in 2008. A multi-stage probabilistic sampling method was used to obtain a total of 203 household interviews. The survey used was based on a culturally adapted version of the Complementary and Alternative Medicine Supplement of the 2007 National Health Interview Survey (NHIS), conducted by the U.S. Department of Health and Human Services. The statistical analysis included means, frequency distributions, and a multiple logistic regression model. Results: The prevalence rates of CAM use ranged from 55.7% to 92.1%, depending on the modalities included under CAM. The most frequently reported medical conditions treated with CAM included back problems, headaches, allergies, anxiety, and depression. Sixty-four percent of the respondents had not informed their physicians that they used CAM. The results showed a marginal association (0.05<p<0.1) between using CAM, being female, having a high level of education, having a family income level of 12,000 to 23,999 (based on reference value) and having insurance coverage for CAM. Conclusion: The results suggest that a relatively large segment of the Bayamón population used one or more CAM modalities in the year prior to the survey. The findings suggest that the prevalence rates of CAM use change depending on which therapeutic modalities are included when “CAM” is being defined. The health issues treated with CAM were associated with chronic conditions. The large portion of respondents not disclosing their use of CAM to their physicians is worrying in terms of patient safety.